Study on Thermal Deformation Behavior and Thermal Processing Map of a New Al-Li Alloy - Daoqi Chen; Xinyang Han; Yinggan Zhang; Yan Liu; Junfeng Chen (Crystals)
As a representative third-generation Al-Li alloy, 2A97 alloy has attracted significant attention for applications in aeronautics and astronautics, but its poor hot workability and complex thermal deformation behavior, which make for difficult optimization, significantly limit its widespread industrial utilization. In this study, the thermal deformation behavior of 2A97 Al-Li alloy was systematically investigated via thermal compression tests conducted over a temperature range of 260–460 °C and strain rates ranging from 0.001 s−1 to 1 s−1. The effects of deformation parameters on the alloy’s microstructural evolution were examined using electron backscatter diffraction (EBSD) and transmission electron microscopy (TEM). Based on the dynamic materials model, a constitutive equation was established by analyzing the stress–strain data under various thermal deformation conditions. Furthermore, a thermal processing map was compiled to analyze the effects of the temperature and strain rate on the power dissipation efficiency and flow instability factor. The thermal deformation mechanisms were identified through combined analysis of the thermal processing map and microstructural features. Results indicate that the fraction of low-angle grain boundaries increases with a rising lnZ value (Zener–Hollomon parameter) during the thermal compression process. Dynamic recrystallization is the main deformation mechanism of 2A97 Al-Li alloy in the stable region, whereas the alloy exhibits flow localization in the unstable region. According to the thermal processing map, the optimal hot working windows for the 2A97 Al-Li alloy were determined to be (1) 360–460 °C at strain rates of 0.05 s−1–1 s−1, and (2) 340–420 °C at strain rates of 0.001 s−1–0.005 s−1. These conditions offer favorable combinations of microstructure and deformation stability, providing critical guidance for the thermo-mechanical processing of 2A97 alloy.